2016
DOI: 10.1002/sim.7171
|View full text |Cite
|
Sign up to set email alerts
|

One-stage individual participant data meta-analysis models: estimation of treatment-covariate interactions must avoid ecological bias by separating out within-trial and across-trial information

Abstract: Stratified medicine utilizes individual‐level covariates that are associated with a differential treatment effect, also known as treatment‐covariate interactions. When multiple trials are available, meta‐analysis is used to help detect true treatment‐covariate interactions by combining their data. Meta‐regression of trial‐level information is prone to low power and ecological bias, and therefore, individual participant data (IPD) meta‐analyses are preferable to examine interactions utilizing individual‐level i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
137
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(141 citation statements)
references
References 56 publications
2
137
1
Order By: Relevance
“…The presented methods assume that within‐trial interactions and across‐trial interactions are equivalent. If ecological bias is at play, across‐trial information may be biased and may differ from interactions found within trials . The NMA models that separate within‐trial and across‐trial interaction have been previously proposed to explore biases .…”
Section: Discussionmentioning
confidence: 99%
“…The presented methods assume that within‐trial interactions and across‐trial interactions are equivalent. If ecological bias is at play, across‐trial information may be biased and may differ from interactions found within trials . The NMA models that separate within‐trial and across‐trial interaction have been previously proposed to explore biases .…”
Section: Discussionmentioning
confidence: 99%
“…One of the big advantages of IPD MA over aggregate data MA is the greater power that it affords for investigating treatment and patient‐level covariate interactions . To explore how the treatment effect may vary in relation to a patient‐level covariate, a TCI can be fitted . The power to detect a TCI will depend on the distribution of the covariate within each study …”
Section: Introductionmentioning
confidence: 99%
“…For example, an IPD MA comparing 2 antiepileptic drugs as monotherapy for controlling seizures originally combined the within‐ and across‐trial interactions and identified an interaction between treatment and age . However, a recent reanalysis separating out the within‐ and across‐trial interactions no longer indicated an interaction between treatment and age on the basis of the within‐trial interaction only …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations